Distribution and antifungal susceptibility of candida species isolated from blood culture - Selim Gorgun; Melek Bilgin; Suleyman Sirri Kilic (Journal of the Pakistan Medical Association, 2021)
Objective: The aim of this study is to determine the distribution of samples exhibiting Candida growth among the blood cultures, and the antifungal susceptibility. Methods: The retrospective study was conducted in Samsun Training and Research Hospital, Samsun, Turkey from January to December, 2018 and comprised immunosuppressed patients with sepsis. Ethical approval was obtained and consent was taken from all patients. Yeast growths were typed by means of colony morphology, germ tube formation and the VITEK 2 system. Their susceptibilities tests were determined using the same automatized system. Resistance strains were also tested using the dilution method. Results: Of the 50 patients, 19(38%) were females and 31(62%) were males. The overall mean age was 60.84 ± 22.05 years. 31 (62%) of the samples were received from intensive care units, 14 (28%) from the palliative care unit, and five from other inpatients. In our study, most common among our isolates was C. albicans, and C. parapsiosis was most common among non-albicans species. Resistance to antifungals was observed in 28% of Candida isolates. Of the total isolates, %10 were found to be naturally resistant to fluconazole, 8% to voriconazole, 4% to flucytosine, and amphotericin B. The high resistance rate for fluconazole in Candida species is noteworthy. The findings obtained through both the dilution method and the automatized system were consistent. Continuou....